The role of pentahelix and digital marketing in developing Lubuak Mande Rubiah destination - Lola Ruliyani; I Made Darma Oka; I Ketut Budarma; I Ketut Suparta (International Journal of Green Tourism Research and Applications, 2022)
This research is to examine the role of pentahelix in building digital marketing in Lubuak Mande Rubiah destination, West Sumatera, Indonesia. It uses a qualitative approach. The data used are participant observation, in-depth interviews, and focus group discussions. The results of research show that the role of pentahelix in building digital marketing in Lubuak Mande Rubiah is that the government plays a role in making regulations to promote people's welfare. Padang city government has made regulations on the management of tourist destinations. Tourism actors collaborate with Pokdarwis and other stakeholders. The digital marketing model of tourist attraction destinations are expanding networks, promoting, and maintaining collaboration with the community, government, tourism actors, academics and media to support improving the quality of facilities and infrastructure.